Studies on isolation and structural identification of saponins from the herb Hylomecon japonica and their bioactivities. (September 2021) - Li, Fei; Wu, Si-Tong; Qu, Ming-Hui; Wang, Yi-Xiao; Ma, Chun-Liu; Yu, Bai-Hong; Wang, Guang-Shu
Abstract: Three undescribed oleanane type triterpenoid saponins (1–3), along with one known saponin (4) were isolated from the whole herb of Hylomecon japonica. Their structures were elucidated by analysis of 1D and 2D-NMR ( 1 H– 1 H COSY, HSQC, and HMBC) spectroscopic data, mass spectrometry (HR-ESI-MS) and chromatographic date (GC and LC) as 3- O -β-d -glucopyranosyl-(1 → 2)-β-d -glucuronopyranosyl gypsogenin 28- O -β-d -galactopyranosyl-(1 → 3)-[β-d -xylopyranosyl-(1 → 4)]-α-l -rhamnopyranosyl-(1 → 2)-β-l -arabinopyranosyl ester (1), 3- O -β-d -galactopyranosyl-(1 → 2)-β-d -glucuronopyranosyl gypsogenin 28- O -α-l -arabinopyranosyl-(1 → 3)-[β-d -xylopyranosyl-(1 → 4)]-α-l -rhamnopyranosyl-(1 → 2)-β-l -arabinopyranosyl ester (2), 3- O -β-d -galactopyranosyl-(1 → 2)-β-d -glucuronopyranosyl gypsogenin 28- O -β-d -galactopyranosyl-(1 → 3)-[β-d -xylopyranosyl-(1 → 4)]-α-l -rhamnopyranosyl-(1 → 2)-β-d -galactopyranosyl ester (3), 3- O -β-d -galactopyranosyl-(1 → 2)-[α-l -arabinopyranosyl-(1 → 3)]-β-d -glucuronopyranosyl gypsogenin 28- O -β-d -glucopyranosyl-(1 → 3)-[β-d -xylopyranosyl-(1 → 4)]-α-l -rhamnopyranosyl-(1 → 2)-β-d -fucopyranosyl ester (4). All saponins possess a partial sequence β-d -galactopyranosyl-(1 → 2)-β-d -glucuronopyranosyl at C-3 of the aglycon. Compound 1 has cytotoxic activity against human colon cancer cell lines HT29, 3 against human gastric cancer cell lines AGS, and 4 against human lung cancer cell lines A549, AGS and HT29. Among them, compounds 3 and 4 showed significant inhibitory effect against AGS with IC50 value of 6.01 ± 1.4 μM, 3.66 ± 1.8 μM, respectively. These results represent a contribution to the chemotaxonomy of the saponins of Hylomecon japonica and their bioactivities. Graphical abstract: Image 1 Highlights: Three undescribed oleanane-type triterpenoid saponins, were isolated from Hylomecon japonica. Their structures were elucidated by 1D, 2D-NMR and HRESI-MS analyses. Compound 1 has cytotoxic activity against human colon cancer cell lines HT29, 3 against human gastric cancer cell lines AGS, and 4 against human lung cancer cell lines A549, AGS and HT29. Among them, compounds 3 and 4 showed significant inhibitory effect against AGS with IC50 value of 6.01 ± 1.4 μM, 3.66 ± 1.8 μM, respectively.